Sassy : Little Sister is not my name - Draper, Sharon M. (Sharon Mills) (New York : Scholastic Press, 2009)
Fashion-savy Sassy does not like being the smallest student in her fourth-grade class, until a family emergency calls for a pint-sized hero.
630
Accelerated Reader AR
Keywords: Size -- Juvenile fiction; Self-acceptance -- Juvenile fiction; Families -- Juvenile fiction; African Americans -- Juvenile fiction; Size -- Fiction; Self-acceptance -- Fiction; Family life -- Fiction; African Americans -- Fiction